CHAPTER 2 RevIEw precalculus
y = (x+2)2
y = (x-2)2 -1
y = -(x+1)2 + 3
4) The number of horsepower H required to overcome wind drag on a certain car is approximated by H(s) = 0.002s2 + 0.05s - 0.029 , 0 < s < 100 where s is the speed of the car in miles per hour. a) Use a graphing calculator to graph. b) Estimate the maximum speed of the car if the power required to overcome wind drag is not to exceed 10 horsepower. Round your answer to the nearest tenth.
4) The number of horsepower H required to overcome wind drag on a certain car is approximated by H(s) = 0.002s2 + 0.05s - 0.029 , 0 < s < 100 where s is the speed of the car in miles per hour. a) Use a graphing calculator to graph. b) Estimate the maximum speed of the car if the power required to overcome wind drag is not to exceed 10 horsepower. Round your answer to the nearest tenth.
4) The number of horsepower H required to overcome wind drag on a certain car is approximated by H(s) = 0.002s2 + 0.05s - 0.029 , 0 < s < 100 where s is the speed of the car in miles per hour. a) Use a graphing calculator to graph. b) Estimate the maximum speed of the car if the power required to overcome wind drag is not to exceed 10 horsepower. Round your answer to the nearest tenth.
4) The number of horsepower H required to overcome wind drag on a certain car is approximated by H(s) = 0.002s2 + 0.05s - 0.029 , 0 < s < 100 where s is the speed of the car in miles per hour. a) Use a graphing calculator to graph. b) Estimate the maximum speed of the car if the power required to overcome wind drag is not to exceed 10 horsepower. Round your answer to the nearest tenth. 59.4 MPH
5) f(x) = x2 - 16
5) f(x) = x2 - 16 = (x )(x )
5) f(x) = x2 - 16 = (x - 4)(x + 4)
5) f(x) = x2 - 16 = (x - 4)(x + 4) zeros: 4, -4
6) f(x) = x2 + 12x + 36
6) f(x) = x2 + 12x + 36 = (x )(x )
6) f(x) = x2 + 12x + 36 = (x + 6)(x + 6)
6) f(x) = x2 + 12x + 36 = (x + 6)(x + 6) zeros: -6, -6
7) f(x) = 2x2 - 14x + 24
7) f(x) = 2x2 - 14x + 24 = 2( )
7) f(x) = 2x2 - 14x + 24 = 2(x2 - 7x + 12)
7) f(x) = 2x2 - 14x + 24 = 2(x2 - 7x + 12) = 2(x )(x )
7) f(x) = 2x2 - 14x + 24 = 2(x2 - 7x + 12) = 2(x - 4)(x - 3)
7) f(x) = 2x2 - 14x + 24 = 2(x2 - 7x + 12) = 2(x - 4)(x - 3) zeros: 4, 3
8) f(x) = x4 - x3 - 20x2
8) f(x) = x4 - x3 - 20x2 = x2( )
8) f(x) = x4 - x3 - 20x2 = x2(x2 - x - 20x)
8) f(x) = x4 - x3 - 20x2 = x2(x2 - x - 20x) = x2(x )(x )
8) f(x) = x4 - x3 - 20x2 = x2(x2 - x - 20x) = x2(x + 4)(x - 5)
8) f(x) = x4 - x3 - 20x2 = x2(x2 - x - 20x) = x2(x + 4)(x - 5) = (x)(x)(x + 4)(x - 5)
8) f(x) = x4 - x3 - 20x2 = x2(x2 - x - 20x) = x2(x + 4)(x - 5) = (x)(x)(x + 4)(x - 5) zeros: 0, 0, -4, 5
Find a polynomial with the following zeros. 9) -7, 2
Find a polynomial with the following zeros. 9) -7, 2 (x - -7)(x - 2)
Find a polynomial with the following zeros. 9) -7, 2 (x - -7)(x - 2) (x + 7)(x - 2)
Find a polynomial with the following zeros. 9) -7, 2 (x - -7)(x - 2) (x + 7)(x - 2) x2 - 2x + 7x - 14
Find a polynomial with the following zeros. 9) -7, 2 (x - -7)(x - 2) (x + 7)(x - 2) x2 - 2x + 7x - 14 x2 + 5x - 14
10) 0, 4
10) 0, 4 (x - 0)(x - 4)
10) 0, 4 (x - 0)(x - 4) x(x - 4)
10) 0, 4 (x - 0)(x - 4) x(x - 4) x2 - 4x
What does the graph of each function look like? (circle two for each) 11) f(x) = -x2 + 6x + 9 rises to the left rises to the right falls to the left falls to the right
What does the graph of each function look like? (circle two for each) 11) f(x) = -x2 + 6x + 9 rises to the left rises to the right falls to the left falls to the right
What does the graph of each function look like? (circle two for each) 11) f(x) = -x2 + 6x + 9 rises to the left rises to the right falls to the left falls to the right
12) f(x) = 0.5x3 + 2x rises to the left rises to the right falls to the left falls to the right
12) f(x) = 0.5x3 + 2x rises to the left rises to the right falls to the left falls to the right
12) f(x) = 0.5x3 + 2x rises to the left rises to the right falls to the left falls to the right
13) f(x) = 6(x4 + 3x2 + 2) rises to the left rises to the right falls to the left falls to the right
13) f(x) = 6(x4 + 3x2 + 2) rises to the left rises to the right falls to the left falls to the right
13) f(x) = 6(x4 + 3x2 + 2) rises to the left rises to the right falls to the left falls to the right
14) f(x) = -x5 - 7x + 10 rises to the left rises to the right falls to the left falls to the right
14) f(x) = -x5 - 7x + 10 rises to the left rises to the right falls to the left falls to the right
14) f(x) = -x5 - 7x + 10 rises to the left rises to the right falls to the left falls to the right
Use long division to simplify. 15) (2x3 - 3x2 - 50x + 75) / (2x - 3)
Use long division to simplify. 15) (2x3 - 3x2 - 50x + 75) / (2x - 3) 2x - 3 2x3 - 3x2 - 50x + 75
Use long division to simplify. 15) (2x3 - 3x2 - 50x + 75) / (2x - 3) x2 2x - 3 2x3 - 3x2 - 50x + 75
Use long division to simplify. 15) (2x3 - 3x2 - 50x + 75) / (2x - 3) x2 2x - 3 2x3 - 3x2 - 50x + 75 2x3 - 3x2
Use long division to simplify. 15) (2x3 - 3x2 - 50x + 75) / (2x - 3) x2 2x - 3 2x3 - 3x2 - 50x + 75 2x3 - 3x2 0 0
Use long division to simplify. 15) (2x3 - 3x2 - 50x + 75) / (2x - 3) x2 2x - 3 2x3 - 3x2 - 50x + 75 2x3 - 3x2 0 0 - 50x + 75
Use long division to simplify. 15) (2x3 - 3x2 - 50x + 75) / (2x - 3) x2 - 25 2x - 3 2x3 - 3x2 - 50x + 75 2x3 - 3x2 0 0 - 50x + 75
Use long division to simplify. 15) (2x3 - 3x2 - 50x + 75) / (2x - 3) x2 - 25 2x - 3 2x3 - 3x2 - 50x + 75 2x3 - 3x2 0 0 - 50x + 75 - 50x + 75
Use long division to simplify. 15) (2x3 - 3x2 - 50x + 75) / (2x - 3) x2 - 25 2x - 3 2x3 - 3x2 - 50x + 75 2x3 - 3x2 0 0 - 50x + 75 - 50x + 75 0 0
Use long division to simplify. 15) (2x3 - 3x2 - 50x + 75) / (2x - 3) x2 - 25 2x - 3 2x3 - 3x2 - 50x + 75 2x3 - 3x2 0 0 - 50x + 75 - 50x + 75 0 0
Use synthetic division to simplify. 16) (3x3 - 17x2 + 15x - 25) / (x - 5)
Use synthetic division to simplify. 16) (3x3 - 17x2 + 15x - 25) / (x - 5) 3 -17 15 -25
Use synthetic division to simplify. 16) (3x3 - 17x2 + 15x - 25) / (x - 5) 5 3 -17 15 -25
Use synthetic division to simplify. 16) (3x3 - 17x2 + 15x - 25) / (x - 5) 5 3 -17 15 -25 3
Use synthetic division to simplify. 16) (3x3 - 17x2 + 15x - 25) / (x - 5) 5 3 -17 15 -25 15 3
Use synthetic division to simplify. 16) (3x3 - 17x2 + 15x - 25) / (x - 5) 5 3 -17 15 -25 15 3 -2
Use synthetic division to simplify. 16) (3x3 - 17x2 + 15x - 25) / (x - 5) 5 3 -17 15 -25 15 -10 3 -2
Use synthetic division to simplify. 16) (3x3 - 17x2 + 15x - 25) / (x - 5) 5 3 -17 15 -25 15 -10 3 -2 5
Use synthetic division to simplify. 16) (3x3 - 17x2 + 15x - 25) / (x - 5) 5 3 -17 15 -25 15 -10 25 3 -2 5
Use synthetic division to simplify. 16) (3x3 - 17x2 + 15x - 25) / (x - 5) 5 3 -17 15 -25 15 -10 25 3 -2 5 0
Use synthetic division to simplify. 16) (3x3 - 17x2 + 15x - 25) / (x - 5) 5 3 -17 15 -25 15 -10 25 3 -2 5 0 3x2 - 2x + 5
17) (2x3 + 14x2 - 20x + 7) / (x + 6)
17) (2x3 + 14x2 - 20x + 7) / (x + 6) 2 14 -20 7
17) (2x3 + 14x2 - 20x + 7) / (x + 6) -6 2 14 -20 7
17) (2x3 + 14x2 - 20x + 7) / (x + 6) -6 2 14 -20 7 -12 -12 192 2 2 -32 199
17) (2x3 + 14x2 - 20x + 7) / (x + 6) -6 2 14 -20 7 -12 -12 192 2 2 -32 199 2x2 + 2x - 32 + 199 x+6
Write in completely factored form. Then find all zeros. 18) f(x) = x3 + 4x2 - 25x - 28 Hint: (x - 4) is a factor
Write in completely factored form. Then find all zeros. 18) f(x) = x3 + 4x2 - 25x - 28 Hint: (x - 4) is a factor 1 4 -25 -28
Write in completely factored form. Then find all zeros. 18) f(x) = x3 + 4x2 - 25x - 28 Hint: (x - 4) is a factor 4 1 4 -25 -28
Write in completely factored form. Then find all zeros. 18) f(x) = x3 + 4x2 - 25x - 28 Hint: (x - 4) is a factor 4 1 4 -25 -28 4 32 28 1 8 7 0
Write in completely factored form. Then find all zeros. 18) f(x) = x3 + 4x2 - 25x - 28 Hint: (x - 4) is a factor 4 1 4 -25 -28 4 32 28 1 8 7 0 x2 + 8x + 7
Write in completely factored form. Then find all zeros. 18) f(x) = x3 + 4x2 - 25x - 28 Hint: (x - 4) is a factor 4 1 4 -25 -28 4 32 28 1 8 7 0 x2 + 8x + 7 (x + 1)(x + 7)
Write in completely factored form. Then find all zeros. 18) f(x) = x3 + 4x2 - 25x - 28 Hint: (x - 4) is a factor 4 1 4 -25 -28 4 32 28 1 8 7 0 x2 + 8x + 7 (x + 1)(x + 7) (x - 4)(x + 1)(x + 7)
Write in completely factored form. Then find all zeros. 18) f(x) = x3 + 4x2 - 25x - 28 Hint: (x - 4) is a factor 4 1 4 -25 -28 4 32 28 1 8 7 0 x2 + 8x + 7 (x + 1)(x + 7) (x - 4)(x + 1)(x + 7) zeros: 4, -1, -7
19) f(x) = x4 - 4x3 - 7x2 + 22x + 24 Hint: (x + 2) and (x - 3) are factors
19) f(x) = x4 - 4x3 - 7x2 + 22x + 24 Hint: (x + 2) and (x - 3) are factors 1 -4 -7 22 24
19) f(x) = x4 - 4x3 - 7x2 + 22x + 24 Hint: (x + 2) and (x - 3) are factors 3 1 -4 -7 22 24 3 -3 -30 -24 1 -1 -10 -8 0
19) f(x) = x4 - 4x3 - 7x2 + 22x + 24 Hint: (x + 2) and (x - 3) are factors 3 1 -4 -7 22 24 3 -3 -30 -24 1 -1 -10 -8 0 x3 - x2 - 10x - 8
19) f(x) = x4 - 4x3 - 7x2 + 22x + 24 Hint: (x + 2) and (x - 3) are factors 3 1 -4 -7 22 24 3 -3 -30 -24 1 -1 -10 -8 0 x3 - x2 - 10x - 8 1 -1 -10 -8
19) f(x) = x4 - 4x3 - 7x2 + 22x + 24 Hint: (x + 2) and (x - 3) are factors 3 1 -4 -7 22 24 3 -3 -30 -24 1 -1 -10 -8 0 x3 - x2 - 10x - 8 -2 1 -1 -10 -8
19) f(x) = x4 - 4x3 - 7x2 + 22x + 24 Hint: (x + 2) and (x - 3) are factors 3 1 -4 -7 22 24 3 -3 -30 -24 1 -1 -10 -8 0 x3 - x2 - 10x - 8 -2 1 -1 -10 -8 -2 6 8 1 -3 -4 0
19) f(x) = x4 - 4x3 - 7x2 + 22x + 24 Hint: (x + 2) and (x - 3) are factors 3 1 -4 -7 22 24 3 -3 -30 -24 1 -1 -10 -8 0 x3 - x2 - 10x - 8 -2 1 -1 -10 -8 -2 6 8 1 -3 -4 0 x2 - 3x - 4
19) f(x) = x4 - 4x3 - 7x2 + 22x + 24 Hint: (x + 2) and (x - 3) are factors 3 1 -4 -7 22 24 3 -3 -30 -24 1 -1 -10 -8 0 x3 - x2 - 10x - 8 -2 1 -1 -10 -8 -2 6 8 1 -3 -4 0 x2 - 3x - 4 (x - 4)(x + 1)
19) f(x) = x4 - 4x3 - 7x2 + 22x + 24 Hint: (x + 2) and (x - 3) are factors 3 1 -4 -7 22 24 3 -3 -30 -24 1 -1 -10 -8 0 x3 - x2 - 10x - 8 -2 1 -1 -10 -8 -2 6 8 1 -3 -4 0 x2 - 3x - 4 (x - 4)(x + 1) (x - 4)(x + 1)(x + 2)(x - 3)
19) f(x) = x4 - 4x3 - 7x2 + 22x + 24 Hint: (x + 2) and (x - 3) are factors 3 1 -4 -7 22 24 3 -3 -30 -24 1 -1 -10 -8 0 x3 - x2 - 10x - 8 -2 1 -1 -10 -8 -2 6 8 1 -3 -4 0 x2 - 3x - 4 (x - 4)(x + 1) (x - 4)(x + 1)(x + 2)(x - 3) zeros: 4, -1, -2, 3
Write each complex number in standard form. 20) (3 + 2i) + (5 + i)
Write each complex number in standard form. 20) (3 + 2i) + (5 + i) 8 + 3i
21) (3 + 2i)(5 + i)
21) (3 + 2i)(5 + i) 15 + 3i + 10i + 2i2
21) (3 + 2i)(5 + i) 15 + 3i + 10i + 2i2 15 + 13i + 2i2
21) (3 + 2i)(5 + i) 15 + 3i + 10i + 2i2 15 + 13i + 2i2 15 + 13i + 2(-1)
21) (3 + 2i)(5 + i) 15 + 3i + 10i + 2i2 15 + 13i + 2i2 15 + 13i + 2(-1) 13 + 13i
22) (3 + 2i) (5 + i)
22) (3 + 2i) * (5 - i) (5 + i) * (5 - i)
22) (3 + 2i) * (5 - i) = 15 - 3i + 10i - 2i2 (5 + i) * (5 - i) = 25 + 5i - 5i - i2
22) (3 + 2i) * (5 - i) = 15 - 3i + 10i - 2i2 = 15 + 7i -2(-1)
22) (3 + 2i) * (5 - i) = 15 - 3i + 10i - 2i2 = 15 + 7i -2(-1)
22) (3 + 2i) * (5 - i) = 15 - 3i + 10i - 2i2 = 15 + 7i -2(-1) = 26
22) (3 + 2i) * (5 - i) = 15 - 3i + 10i - 2i2 = 15 + 7i -2(-1) = 26 17 + 7 i 26 26
Find all zeros. Then rewrite the function in completely factored form. 23) f(x) = x2 - 10x + 6
Find all zeros. Then rewrite the function in completely factored form. 23) f(x) = x2 - 10x + 6 A = 1 B = -10 C = 6
Find all zeros. Then rewrite the function in completely factored form. 23) f(x) = x2 - 10x + 6 A = 1 B = -10 C = 6
Find all zeros. Then rewrite the function in completely factored form. 23) f(x) = x2 - 10x + 6 A = 1 B = -10 C = 6
Find all zeros. Then rewrite the function in completely factored form. 23) f(x) = x2 - 10x + 6 A = 1 B = -10 C = 6
Find all zeros. Then rewrite the function in completely factored form. 23) f(x) = x2 - 10x + 6 A = 1 B = -10 C = 6
Find all zeros. Then rewrite the function in completely factored form. 23) f(x) = x2 - 10x + 6 A = 1 B = -10 C = 6 =
Find all zeros. Then rewrite the function in completely factored form. 23) f(x) = x2 - 10x + 6 A = 1 B = -10 C = 6 =
24) f(x) = x2 + 2x + 4
24) f(x) = x2 + 2x + 4 Quadratic Formula
24) f(x) = x2 + 2x + 4 Quadratic Formula ---------> Magic Happens
24) f(x) = x2 + 2x + 4 Quadratic Formula ---------> Magic Happens ------------>
24) f(x) = x2 + 2x + 4 Quadratic Formula ---------> Magic Happens ------------>
25) f(x) = 3x4 - 4x3 + 7x2 + 10x - 4
25) f(x) = 3x4 - 4x3 + 7x2 + 10x - 4
25) f(x) = 3x4 - 4x3 + 7x2 + 10x - 4 -1 3 -4 7 10 -4 -3 7 -14 4 3 -7 14 -4 0 3x3 - 7x2 + 14x - 4
25) f(x) = 3x4 - 4x3 + 7x2 + 10x - 4 -1 3 -4 7 10 -4 -3 7 -14 4 3 -7 14 -4 0 3x3 - 7x2 + 14x - 4
25) f(x) = 3x4 - 4x3 + 7x2 + 10x - 4 3x3 - 7x2 + 14x - 4 -1 3 -4 7 10 -4 -3 7 -14 4 3 -7 14 -4 0 3x3 - 7x2 + 14x - 4
25) f(x) = 3x4 - 4x3 + 7x2 + 10x - 4 3x3 - 7x2 + 14x - 4 -1 3 -4 7 10 -4 1/3 3 -7 14 -4 -3 7 -14 4 1 -2 4 3 -7 14 -4 0 3 -6 12 0 3x3 - 7x2 + 14x - 4 3x2 - 6x + 12
25) f(x) = 3x4 - 4x3 + 7x2 + 10x - 4 3x3 - 7x2 + 14x - 4 -1 3 -4 7 10 -4 1/3 3 -7 14 -4 -3 7 -14 4 1 -2 4 3 -7 14 -4 0 3 -6 12 0 3x3 - 7x2 + 14x - 4 3x2 - 6x + 12 Quadratic Formula
25) f(x) = 3x4 - 4x3 + 7x2 + 10x - 4 3x3 - 7x2 + 14x - 4 -1 3 -4 7 10 -4 1/3 3 -7 14 -4 -3 7 -14 4 1 -2 4 3 -7 14 -4 0 3 -6 12 0 3x3 - 7x2 + 14x - 4 3x2 - 6x + 12 Quadratic Formula -------> Magic Happens
Quadratic Formula -------> Magic Happens -------> 25) f(x) = 3x4 - 4x3 + 7x2 + 10x - 4 3x3 - 7x2 + 14x - 4 -1 3 -4 7 10 -4 1/3 3 -7 14 -4 -3 7 -14 4 1 -2 4 3 -7 14 -4 0 3 -6 12 0 3x3 - 7x2 + 14x - 4 3x2 - 6x + 12 Quadratic Formula -------> Magic Happens -------> x = x =
Quadratic Formula -------> Magic Happens -------> 25) f(x) = 3x4 - 4x3 + 7x2 + 10x - 4 3x3 - 7x2 + 14x - 4 -1 3 -4 7 10 -4 1/3 3 -7 14 -4 -3 7 -14 4 1 -2 4 3 -7 14 -4 0 3 -6 12 0 3x3 - 7x2 + 14x - 4 3x2 - 6x + 12 Quadratic Formula -------> Magic Happens -------> x = x =
26) f(x) = x3 - 4x2 + 6x - 4
26) f(x) = x3 - 4x2 + 6x - 4
26) f(x) = x3 - 4x2 + 6x - 4 2, ____, ____
26) f(x) = x3 - 4x2 + 6x - 4 2, ____, ____ Synthetic Division
26) f(x) = x3 - 4x2 + 6x - 4 2, ____, ____ Synthetic Division ------> x2 - 2x + 2
26) f(x) = x3 - 4x2 + 6x - 4 2, ____, ____ Synthetic Division ------> x2 - 2x + 2 ------> Quadratic Formula
26) f(x) = x3 - 4x2 + 6x - 4 2, 1 + i, 1 - i Synthetic Division ------> x2 - 2x + 2 ------> Quadratic Formula
26) f(x) = x3 - 4x2 + 6x - 4 2, 1 + i, 1 - i (x - 2)(x - 1 - i)(x - 1 + i) Synthetic Division ------> x2 - 2x + 2 ------> Quadratic Formula
Find a polynomial with the following zeros. 27) 2 + 3i, 2 - 3i (x - (2+3i))(x - (2 - 3i)) (x - 2 - 3i)(x - 2 + 3i) x2 - 2x + 3ix
Find a polynomial with the following zeros. 27) 2 + 3i, 2 - 3i (x - (2+3i))(x - (2 - 3i)) (x - 2 - 3i)(x - 2 + 3i) x2 - 2x + 3ix - 2x + 4 - 6i
Find a polynomial with the following zeros. 27) 2 + 3i, 2 - 3i (x - (2+3i))(x - (2 - 3i)) (x - 2 - 3i)(x - 2 + 3i) x2 - 2x + 3ix - 2x + 4 - 6i - 3ix + 6i - 9i2
Find a polynomial with the following zeros. 27) 2 + 3i, 2 - 3i (x - (2+3i))(x - (2 - 3i)) (x - 2 - 3i)(x - 2 + 3i) x2 - 2x + 3ix - 2x + 4 - 6i - 3ix + 6i - 9i2 x2 - 2x + 3ix - 2x + 4 - 6i - 3ix + 6i - 9(-1)
Find a polynomial with the following zeros. 27) 2 + 3i, 2 - 3i (x - (2+3i))(x - (2 - 3i)) (x - 2 - 3i)(x - 2 + 3i) x2 - 2x + 3ix - 2x + 4 - 6i - 3ix + 6i - 9i2 x2 - 2x + 3ix - 2x + 4 - 6i - 3ix + 6i - 9(-1) x2 - 4x + 4 + 9
Find a polynomial with the following zeros. 27) 2 + 3i, 2 - 3i (x - (2+3i))(x - (2 - 3i)) (x - 2 - 3i)(x - 2 + 3i) x2 - 2x + 3ix - 2x + 4 - 6i - 3ix + 6i - 9i2 x2 - 2x + 3ix - 2x + 4 - 6i - 3ix + 6i - 9(-1) x2 - 4x + 4 + 9 x2 - 4x + 13
28) 0, 3, 5i, -5i
28) 0, 3, 5i, -5i (x) (x-3) (x-5i) (x+5i)
28) 0, 3, 5i, -5i (x) (x-3) (x-5i) (x+5i) ( x2 - 3x ) (x2 + 5ix - 5ix - 25i2 )
28) 0, 3, 5i, -5i (x) (x-3) (x-5i) (x+5i) ( x2 - 3x ) (x2 + 5ix - 5ix - 25i2 ) ( x2 - 3x ) (x2 + 25)
28) 0, 3, 5i, -5i (x) (x-3) (x-5i) (x+5i) ( x2 - 3x ) (x2 + 5ix - 5ix - 25i2 ) ( x2 - 3x ) (x2 + 25) x4 + 25x2 - 3x3 - 75x
28) 0, 3, 5i, -5i (x) (x-3) (x-5i) (x+5i) ( x2 - 3x ) (x2 + 5ix - 5ix - 25i2 ) ( x2 - 3x ) (x2 + 25) x4 + 25x2 - 3x3 - 75x x4 - 3x3 + 25x2 - 75x
Find the horizontal asymptotes, vertical asymptotes, and holes for each rational function. 29)
Find the horizontal asymptotes, vertical asymptotes, and holes for each rational function. 29) HA: y = -1 VA: x = -3 Holes: none
Find the horizontal asymptotes, vertical asymptotes, and holes for each rational function. 30)
Find the horizontal asymptotes, vertical asymptotes, and holes for each rational function. 30) HA: y = 4 VA: x = 8 Holes: none
Find the horizontal asymptotes, vertical asymptotes, and holes for each rational function. 31)
Find the horizontal asymptotes, vertical asymptotes, and holes for each rational function. 31) HA: y = 0 VA: x = -3, x = 6 Holes: none
Find the horizontal asymptotes, vertical asymptotes, and holes for each rational function. 32)
Find the horizontal asymptotes, vertical asymptotes, and holes for each rational function. 32) HA: y = 0 VA: x = -1, x = 1 Holes: none
Find the horizontal asymptotes, vertical asymptotes, and holes for each rational function. 33)
Find the horizontal asymptotes, vertical asymptotes, and holes for each rational function. 33) HA: y = 3 VA: none Holes: none
Find the horizontal asymptotes, vertical asymptotes, and holes for each rational function. 34) hint: this one has a hole
Find the horizontal asymptotes, vertical asymptotes, and holes for each rational function. 34) hint: this one has a hole HA: y = 1 VA: x = -1 Holes: x = 1 (x - 4)(x - 1) (x + 1)(x - 1)
Find the horizontal asymptotes, vertical asymptotes, and holes for each rational function. 35) hint: this one has a hole
Find the horizontal asymptotes, vertical asymptotes, and holes for each rational function. 35) hint: this one has a hole HA: y = 1 VA: x = -1.5 Holes: x = 3 (2x - 1)(x - 3) (2x + 3)(x - 3)
36). This table shows the amounts A (in dollars) spent per 36) This table shows the amounts A (in dollars) spent per person on the internet in the United States from 2000 to 2005. Use a graphing calculator to create a scatter plot of the data. Let t represent the year, with t = 0 corresponding to 2000. a) Calculate a quadratic regression line to fit the data. What is its equation? b) Based on your quadratic model, approximate how much was spent on each person in 2008. Year Amount, A (in hours) 2000 3492 2001 3540 2002 3606 2003 3663 2004 3757 2005 3809
36). This table shows the amounts A (in dollars) spent per 36) This table shows the amounts A (in dollars) spent per person on the internet in the United States from 2000 to 2005. Use a graphing calculator to create a scatter plot of the data. Let t represent the year, with t = 0 corresponding to 2000. a) Calculate a quadratic regression line to fit the data. What is its equation? f(x) = 2.36t2 + 53.7t + 3489 b) Based on your quadratic model, approximate how much was spent on each person in 2008. Year Amount, A (in hours) 2000 3492 2001 3540 2002 3606 2003 3663 2004 3757 2005 3809